Implementasi Metode Research and Development Pada Pengembangan Pembelajaran Matematika Berbasis Multimedia - Perdana Wanti, Linda; Sari, Laura (P3M Politeknik Negeri Cilacap, 2021)
Mathematics is a lesson that is still a frightening specter for some students. There are several methods used to make mathematics fun to learn. One of them is to package material in mathematics to be more attractive and interesting, especially for children this can make them become interested in learning mathematics. The developed using research and development methods. This method begins by exploring the problem, collecting data needed, designing the product to be developed, validating the product design, testing the use of the system to be developed, revising the product, testing the product, revising the product and product design if there are errors or deficiencies and the last is mass production of product. This research aims to develop an interactive multimedia-based mathematics learning which can later be optimized to increase student interest in learning mathematics and be used to improve the quality of education.